Quality competition and social welfare in markets with partial coverage: New results - Gregory S. Amacher; Erkki Koskela; Markku Ollikainen (The Research Institute of the Finnish Economy (ETLA), 2003)
We use a vertical product differentiation model under partial market coverage to study the social welfare optimum and duopoly equilibrium when convex costs of quality provision are either fixed or variable in terms of production. We show that, under fixed costs, at the social welfare optimum only one quality variant of the good is provided, while both variants are optimal under variable costs. In the duopoly equilibrium the quality spread is too wide under variable costs, but too narrow under fixed costs, relative to the social optimum. Finally, in both the fixed and variable cost cases, average quality provided by the duopoly equilibrium is too low from the perspective of a social welfare maximizer.
Keywords: L13; D60; 330; Product Differentiation; Partial Market Coverage; Social Welfare; Produktqualität; Produktdifferenzierung; Nichtpreiswettbewerb; Wohlfahrtseffekt